Outcomes of high‐volume bariatric surgery in the public system. Issue 7 (16th October 2015) - Burton, Paul; Brown, Wendy; Chen, Richard; Shaw, Kalai; Packiyanathan, Andrew; Bringmann, Ingra; Smith, Andrew; Nottle, Peter
Abstract: Background: Bariatric surgery has not been widely used in the Australian public health system. As obesity is strongly associated with socio‐economic status, excluding its use from the public system will deny many of the most in‐need access to a potentially very effective treatment. Alternatively, with rigorous follow‐up and behavioural change requirements, highly successful outcomes in the private system may not translate to the public system. Methods: The Alfred Hospital rapidly expanded bariatric surgery from 2007. A 6‐year prospective follow‐up study was conducted with annual review of weight, co‐morbidities, retention in follow‐up, serum HbA1c, quality of life and patient satisfaction. Results: There were 1453 patients. Procedures were predominantly laparoscopic‐adjustable gastric bands ( n = 861). Patient details were age 49 ± 11 years, body mass index 50.7 ± 11.2 kg/m 2 and weight 139.0 ± 30.2 kg. There was no mortality, and mean length of stay was 1.1 ± 1.2 days. Follow‐up was 98% (1 year) and 85% (6 years). Weight loss was 22 ± 13.1 kg (32.8 ± 18% excess weight loss) at 1 and 30.1 ± 16.8 kg (60 ± 28%) at 6 years. The mean number of co‐morbidities was 4.2 ± 1.1 with significant improvements observed. Patient satisfaction was 7.7 ± 2.3 out of 10. Mental and physical summary scores (SF‐36) improved from 41.02 ± 13.17 to 45.50 ± 13.27 ( P < 0.001) and 33.97 ± 10.53 to 44.79 ± 11.19 ( P < 0.001). Conclusions: Patients were older, heavier and suffered more co‐morbid disease than previously reported cohorts. For the first time, excellent outcomes across a range of key quality domains in a large patient cohort have been reported in the public system. High‐volume bariatric surgery in the public system is viable.